التغطية الأخبارية لقضايا القدس في الفضائيات الفلسطينية دراسة تحليلية على فضائيات فلسطين والأقصى وفلسطين اليوم - Mahmoud E. M. Ayyash
Recently, the Israeli plans for the Jerusalem city have become more prominent in order to achieve full control and Judaize it. Therefore, this makes the role of media become a necessary and important tool in the battle to preserve the city. Hence, this study aims to examine the Palestinian channel's coverage about Jerusalem issues and determine the causes and explanations for the differences and similarities among them. For this, and to achieve its objectives, the study used a content analysis method to analyses the main news broadcasts in three Palestinian channels, which are: Palestine, Al Aqsa and Palestine Today TV channels. However, the study examined the main news for thirty days starting from the 1st of July 2017 and finished by the end of the same month. The study showed numerous results which already were discussed with the officials in the TV channels and some specialists in the field of media and Jerusalem affairs. The study concluded that there are significant differences among the channels, in their coverage about Jerusalem issues, the differences not only occur at the quantity level and the time allocated for Jerusalem news, but also in the terminology used, solutions provided and at the content level. The results showed that the difference and similarities could be explained by the different political agendas hold by the channels which link to different Palestinian parties, the different in the news policies adopted by the channels, the range and level of the channels owners’ international relations, the channels’ headquarters geographical place, the channels’ ideological and religious identity, the channels’ objectives, the media laws and the channels’ agreements.